STRATEGI PEMASARAN JASA INFORMASI DI TAMAN BACAAN MASYARAKAT (TBM) RIMBA BULAN KOTA PADANG PANJANG - Wahyuni, Sri; Manita, Rika Jufriazia; Rahmi, Mezi Mulia (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2025)
This study aims to analyze the information service marketing strategies implemented at the Community Reading Center (Taman Bacaan Masyarakat/TBM) Rimba Bulan in Padang Panjang City and to formulate promotional enhancement measures to increase community utilization of literacy services. The research method employed is descriptive qualitative, using observation, in-depth interviews, and documentation techniques. The findings indicate that the TBM has actively promoted its services through both print and digital media, yet it still faces challenges such as limited human resources and budget constraints. Recommendations include intensifying the use of social media, providing digital marketing training for TBM managers, and expanding promotional partnership networks. This study is expected to contribute to the development of more effective and sustainable marketing strategies for information services in community-based libraries.